Construction and efficacy evaluation of a group psychological training program for enhancing the sense of meaning in life for transitional retired soldiers - XIA Tingting; XIA Tingting; YANG Yi; YANG Wanjun (陆军军医大学学报)
Objective To develop a group psychological training program to cultivate a sense of meaning in life for retired soldiers during the transitional period, and to explore the efficacy of the training. Methods A psychological training program for retired soldiers during the transitional period was developed based on Delphi method. A total of 64 retired soldiers who participated in a retirement training in transitional period were subjected through cluster sampling in a certain city in Shandong province and assigned into a training group (n=31) and a control group (n=33). The training group attended group psychological training based on the developed training program (twice a week, 1.5~2 h each time, for 4 weeks), and the control group received routine adaptive training for retirement. Purpose in Life (PIL) Test, Chinese Perceived Stress Scale (CPSS) and Social Adaptability Scale (SAS) were used to survey the participants before (T1), and at the end of (T2) and 1 month after the training (T3). Results ① The results of 2 rounds of expert consultation showed that the coefficient of authority (Cr) was 0.89, and the Kendall's coefficient (ω) of the 2 rounds was 0.134 and 0.204, respectively (P < 0.001), with a coefficient of variation ranging from 0.05 to 0.14. The prepared group psychological training program consisted of 3 first-level indexes, 6 second-level indexes, and 24 third-level indexes. ② The results of the interaction between group and time after training showed that the training group had significantly higher total score and score of each dimension in sense of meaning in life, and increased total score of social adaptability, but lower total score of perceived stress when compared with the control group (all P < 0.001). ③ The results of group main effect after training indicated that obviously higher total score and score of each dimension in sense of meaning in life (P < 0.01), elevated total score of social adaptability (P < 0.01), and reduced total score of perceived stress (P < 0.001) were observed in the training group than the control group. ④ The results of the post-training time main effect revealed that the training group had notably higher total score and score of each dimension in sense of meaning in life (P < 0.05), increased total score of social adaptability (P < 0.001), and decreased total score of perceived stress (P < 0.001) when compared with the control group. Conclusion Our developed group psychological training can significantly improve the sense of meaning in life, reduce perceived stress and improve their social adaptation ability for retired soldiers during the transitional period.